Belloc's Anti-State Postliberal Distributism - Plato, Alex M. (American catholic philosophical quarterly, 2025)
I examine various striking ideas in Belloc's writings which indicate separately and jointly confirm that his distributism is a radical and far-reaching social philosophy which undergirds all-encompassing reform of the social order: religious, cultural, political, and economic. In short, Belloc seems to be an anti-state postliberal distributist. Belloc explains that the deeper reform of religion and culture are integral to achieving the oft-repeated economic goals familiar to those defending or criticizing distributism. If I'm right, then distributists can follow Belloc’s lead in opposing the embodied tradition of liberalism in both theory and practice (i.e., in being postliberals) and embark upon the distributist reform program which is designed to translate (however quickly or slowly and according to justice and prudence) the liberal order out of existence, including both the Modern State and the Market System, and into a Christian social order, a new polity.